(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Parental Involvement plays a significant part in children’s growth and development. This study investigated the parental involvement on their children’s developmental skills. A total of 30 parents of Pilgrim Christian College participated in the study amidst the global pandemic. A questionnaire containing the items from Epstein’s parental involvement, and ECCD checklist of basic education’s developmental skills. Descriptive statistics and multiple regression were used to organize the data. Findings reveal that the components of parental involvement were rated as very high, except volunteerism which was rated as high. The children’s developmental domains were rated as very high. Parental involvement significantly influenced the children’s developmental skills. The study affirms that parental involvement has greatly contributed to the development of their children’s skills, and it points to the need for the development of the children’s emotions. Parents may continue their involvement for their children’s education especially in getting and returning modules and other activities.